KONSTRUKSI HUKUM PERLINDUNGAN KONSUMEN TERHADAP DARK PATTERN PADA APLIKASI FINTECH - Wisnu Cahyo Apriliyadi; Hasnah Aziz; Muhammad Fajar Alfahimi; Aditya Putra Setyawan; Ahiruddin (Berajah Journal, 2026)
The development of financial technology (fintech) in Indonesia has significantly transformed the financial transaction landscape. However, behind the convenience offered, manipulative practices known as dark patterns have emerged in fintech application interfaces. These practices refer to user interface design elements deliberately exploited to manipulate users into making unintended decisions, such as subscribing to paid services, consenting to personal data usage, or conducting specific financial transactions. This study aims to construct a legal framework for consumer protection against dark patterns in fintech applications in Indonesia by analyzing existing legal provisions and identifying regulatory gaps. The research method used is normative legal research with a statutory, conceptual, and comparative approach. The results indicate that Law Number 8 of 1999 on Consumer Protection, Law Number 11 of 2008 on Information and Electronic Transactions as amended by Law Number 19 of 2016, and regulations of the Financial Services Authority (OJK) have not explicitly regulated dark patterns as a form of unfair trading practice. This study recommends the need to amend the Consumer Protection Law to accommodate specific regulation of dark patterns, strengthening the OJK's authority in overseeing fintech application interface design practices, and establishing binding ethical interface design codes for fintech providers.